Heterotopic Gastric Mucosa Causing Rectal Bleeding in a Young Child. Issue 2 (25th May 2022) - Patricia-Rae Meyer, Blake; Nguyen, Johnny; Wilsey, Michael; Karjoo, Sara
Abstract : Heterotopic gastric mucosa (HGM) in the colon and small bowel is a very rare finding. We report a case of HGM in the rectum of an 8-year-old child with a history of eosinophilic esophagitis after having a colonoscopy to evaluate for inflammatory bowel disease. The colonoscopy was normal except for rectal tissue erythema and edema. Inflammatory bowel disease has been reported in some cases of children with eosinophilic changes of the esophagus. The child had intermittent rectal bleeding thought to be due to constipation. Interestingly, when the patient was placed on a proton pump inhibitor for the treatment of eosinophilic esophagitis, the rectal bleeding decreased. After our patient ceased proton pump inhibitor therapy, he experienced a large amount of rectal bleeding. Histological findings revealed HGM in the colon/rectum. An extensive review of the incidence, diagnosis, and treatment is discussed.